The interpretation of oriental model of the world’s intellectual construction in Lesya Ukrayinka’s dramatic poems (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the specificity of representation of The Egyptian Cultural Space in Lesya Ukrayinka’s dramaturgic  heritage. The linguo-aesthetic dominants that form an intellectual basis of authoress`s literary works are analyzed.
Keywords: oriental text; intellectualization of the literary language; verbalization; cultural space; linguo-aesthetical sign of culture; conceptual picture of the world